Tobacco smoking and HIV-related immunologic and virologic response among individuals of the Canadian HIV Observational Cohort (CANOC). Issue 8 (3rd August 2022) - McClean, Alison R.; Kooij, Katherine W.; Trigg, Jason; Ye, Monica; Sereda, Paul; McLinden, Taylor; Bacani, Nicanor; Aran, Niloufar; Thomas, Réjean; Wong, Alexander; Klein, Marina B.; Hull, Mark; et al.
ABSTRACT: We assessed the relationship between tobacco smoking and immunologic and virologic response among people living with HIV (PLWH) initiating combination antiretroviral therapy (cART) in the Canadian HIV Observational Cohort (CANOC). Positive immunologic and virologic response, respectively, were defined as ≥50 cells/mm 3 CD4 count increase (CD4+) and viral suppression ≤50 copies/mL (VL+) within 6 months of cART initiation. Using multinomial regression, we examined the relationship between smoking, immunologic, and virologic response category. Model A adjusted for birth sex, baseline age, enrolling province, and era of cohort entry; models B and C further adjusted for neighbourhood level material deprivation and history of injection drug use (IDU), respectively. Among 4267 individuals (32.7%) with smoking status data, concordant positive (CD4+/VL+) response was achieved by 64.2% never, 66.9% former, and 59.4% current smokers. In the unadjusted analysis, current smoking was significantly associated with concordant negative response (odds ratio [OR] 1.85, 95% confidence interval [CI] 1.40–2.45). Similarly, models A and B showed an increased odds of concordant negative response in current smokers (adjusted OR [aOR] 1.78, 95% CI 1.32–2.39 and 1.74, 95% CI 1.29–2.34, respectively). The association between current smoking and concordant negative response was no longer significant in model C (aOR 1.18, 95%CI 0.85–1.65).